2019
DOI: 10.1002/dmrr.3194
|View full text |Cite
|
Sign up to set email alerts
|

Association between insulin resistance and haematological parameters: A cohort study from adolescence to adulthood

Abstract: Background:The aim of this study was to quantify the relationship between insulin resistance and haematological parameters from adolescence to adulthood. Methods:Participants from the EPITeen cohort were evaluated at 13, 17, and 21 years, through standardized procedures. A fasting blood sample was obtained, and insulin resistance was evaluated by the homeostatic model assessment (HOMA-IR). The cross-sectional association between HOMA-IR and haematological parameters at 21 years was quantified in 1671 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Other studies demonstrated that circulating RBC could be used to re ect short-term uctuations in insulin-receptor a nity and long-term changes in receptor concentration [37]. Accumulating population-based evidence further support that high levels of RBC count and Hb are positively associated with underlying pathophysiological changes of hyperglycemia, including insulin resistance [14,15], β-cell dysfunction [15], and decreased insulin sensitivity [15]. HbA1c level is also affected by RBC lifespan and positively correlated with the RBC count since the lifespan of RBCs can directly affect the reaction time of glycosylation between Hb and blood glucose [38].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies demonstrated that circulating RBC could be used to re ect short-term uctuations in insulin-receptor a nity and long-term changes in receptor concentration [37]. Accumulating population-based evidence further support that high levels of RBC count and Hb are positively associated with underlying pathophysiological changes of hyperglycemia, including insulin resistance [14,15], β-cell dysfunction [15], and decreased insulin sensitivity [15]. HbA1c level is also affected by RBC lifespan and positively correlated with the RBC count since the lifespan of RBCs can directly affect the reaction time of glycosylation between Hb and blood glucose [38].…”
Section: Discussionmentioning
confidence: 95%
“…Hb is the speci c protein molecule in red blood cell (RBC) carrying almost all of oxygen molecules and is closely related to the number of RBC [13]. Previous studies have con rmed that RBC count is signi cantly associated with insulin resistance [14], β-cell dysfunction [15], and the incidence of type 2 diabetes [16], which suggest that peripheral RBC count may also play a role in GDM development. However, few studies have examined the relationship between RBC count in early pregnancy and the risk of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous studies on the association between platelets and UACR are very few; nevertheless, they show an independent relationship between mean platelet volume, increased albuminuria, and other microvascular complications such as retinopathy in T2DM [ 60 , 61 ]. Platelet activity plays a major role in the pathogenesis of endothelial injury and vascular disease [ 62 ]; moreover, it has been associated with hyperglycemia [ 63 ] and insulin resistance [ 64 , 65 , 66 ], which in turn are associated with increased albuminuria [ 11 ]. Although platelet count seems to share common pathways to other risk factors associated with increased albuminuria, in the current analysis, such association was independent of insulin resistance, diabetes, liver fibrosis, and other potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Regarding blood tests, previous studies have shown that blood cells, including leukocytes (WBC), erythrocytes (RBC), platelets (PLT), and hemoglobin (HGB), are associated with IR. [26][27][28] These are also tests that can be performed in most primary care hospitals during routine physical examinations, and even by using peripheral blood in many places, which is very child-friendly. In addition, there are also some biochemical tests and genetic tests that have been shown to correlate with IR.…”
Section: Feature Selectionmentioning
confidence: 99%